The Influence of Supervision and Task Planning on the Performance of Agencies in the Operational Administration Planning Bureau of the Mobile Brigade Corps of the National Police Republic of Indonesia - Febri Ayu Wanda; Kemal Taufik; Sri Wahyuningsih (Dinasti Publisher, 2026)
The objectives of this study: 1) To determine the effect of Supervision on the Performance of the institution in the Rorenminops Korbrimob Polri, 2) To determine the effect of Task Planning on the Performance of the institution in the Rorenminops Korbrimob Polri, 3) To determine the effect of Supervision and Task Planning on the Performance of the institution. Career development through certification, the quality of certification implementation and the work spirit of Polri educators. The results of the partial test show that the Task Planning variable (X2) has a positive and significant effect on the Performance of the Institution (Y), which is indicated by the t-value of 8.186 which is greater than the t-table of 1.998. This confirms that clear, systematic, and measurable task planning is crucial for the successful implementation of tasks and the optimal achievement of agency performance. Simultaneous supervision and task planning significantly influence agency performance. Based on the results of the simultaneous test (F test), the calculated F value was 131.225, which is greater than the F table of 2.75 with a significance level of 0.000 <0.05. This indicates that the variables of supervision (X1) and task planning (X2) together have a positive and significant influence on agency performance (Y) in the Operational Administration Planning. The R Square value of 0.816 indicates that 81.6% of the variation in agency performance, while the remaining 18.4% is influenced by other factors.